Kinerja Ruas Jalan Bhayangkara Setelah Penerapan Sistem Satu Arah di Kawasan Malioboro Kota Yogyakarta - Kennyzyra, Muhammad; Miftahul Fauziah; Aisyah Nur Jannah (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Congestion is a form of transportation problem that occurs in the Malioboro area of ​​Yogyakarta City. One form of effort to overcome the problem of congestion in the Malioboro area is the implementation of the One Way System. This research aims to analyze and determine the comparison of road performance on Jalan Bhayangkara road section, Pajeksan road section, Margo Mulyo road section, and K.H. Ahmad Dahlan road section before and after the implementation of One Way System in the Malioboro area. Traffic performance analysis was carried out based on MKJI 1997 and modeling was carried out with PTV VISSIM. The implementation of SSA in the Malioboro area caused the average saturation value of the four road sections to increase by 3% and caused the average speed value of the four road sections to decrease by 2%. Therefore, it can be stated that the implementation of One Way System is not the main solution in solving transportation problems.